(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Abstract | This essay examines the encounter between Western countercultural groups and the urban landscape of East Berlin in the years immediately following the fall of the Berlin Wall in 1989. Focusing on squatted houses, the underground techno scene, and experimental art projects, the essay argues that countercultural groups who were active in East Berlin in the early 1990s developed a peculiar set of practices that were characterized both by their campy aesthetics and by their temporal indeterminacy. The essay posits that these experimental temporal practices were only possible due to the layered historicity of urban space in the dilapidated, inner-city neighbourhoods of East Berlin. Résumé | Cet essai étudie la rencontre entre les groupes contre-culturels Occidentaux et le paysage urbain de Berlin-Est suite à la chute du Mur de Berlin en 1989. A travers une analyse des squats, de la scène techno « underground » et des projets d’art expérimental, l’essai soutient que les groupes contre-culturels actifs dans le Berlin-Est du début des années 1990 ont développé un ensemble de pratiques caractérisé à la fois par leur esthétique maniérée et leur indétermination temporelle. L’essai avance que seule l’historicité imbriquée de l’espace urbain dans les quartiers pauvres et dilapidés du Berlin-Est a rendu possible ces pratiques temporelles expérimentales.